2012
DOI: 10.1111/j.1467-8543.2012.00890.x
|View full text |Cite
|
Sign up to set email alerts
|

Wage Effects of On‐the‐Job Training: A Meta‐Analysis

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 68 publications
2
40
0
3
Order By: Relevance
“…Moreover, the reduced form estimated typically depends on the data available, which in turn differs across data sets and countries. For a similar point see Haelermans and Borghans (2012). 8 Oosterbeek (2002, 2004) use two different methods to estimate the returns to training in Holland.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the reduced form estimated typically depends on the data available, which in turn differs across data sets and countries. For a similar point see Haelermans and Borghans (2012). 8 Oosterbeek (2002, 2004) use two different methods to estimate the returns to training in Holland.…”
Section: Resultsmentioning
confidence: 99%
“…The most comprehensive study that considers the impact of firm-sponsored training on wages is a recent overview analysis of 71 sets of results from 38 studies [8]. The analysis shows an average wage increase of 2.6% for each occurrence of training.…”
Section: Effects Of Training On Wagesmentioning
confidence: 99%
“…Bartel 1994;Almeida and Carneiro 2008). A meta-analysis by Haelermans and Borghans (2012) reported that the average effect on wage returns of workers who received OJT is 2.6 % per course. Fewer studies exploit exogenous changes in the decision to estimate the effects of training and, in contrast, find relatively small impacts (e.g.…”
Section: Source: Authorsʼ Elaborationmentioning
confidence: 99%